Clinical advances and challenges in targeting FGF/FGFR signaling in lung cancer - Mei Peng; Jun Deng; Xiangping Li (Molecular Cancer)
Abstract Fibroblast growth factors (FGFs) and their receptors regulate numerous cellular processes, such as metabolism and signal transduction, but can also drive tumorigenesis. Specifically, in lung cancer, the overexpression of FGFs, as well as the amplification, mutation and fusion of FGFR genes, are closely linked to the initiation, progression and resistance of the disease, suggesting that targeting FGF/FGFR is an attractive therapeutic strategy for lung cancer treatment. Nintedanib, a multitarget tyrosine kinase inhibitor (TKI) used in combination with docetaxel, has shown some success as a second-line therapy for lung cancer. However, clinical trials evaluating other FGFR inhibitors have yielded mixed results, indicating substantial complexity in targeting aberrant FGF/FGFR signaling. In this review, we describe the aberrations in FGF/FGFR signaling in lung cancer and summarize the clinical efficacy of FGFR inhibitors, such as multitarget TKIs, selective FGFR-TKIs and biological agents. We also discuss various challenges associated with FGFR targeting in lung cancer, including precision patient selection, toxicity and resistance. Finally, we provide perspectives on future directions, namely, developing novel FGFR-targeting drugs, such as FGFR degraders and more specific FGFR-TKIs, adopting combination therapy and targeting FGFs.